Analysis Of Debt To Total Asset, Return On Asset, Cash Ratio And Their Impact On Dividend Payout Ratio With Firm Size As Intervening Variable In Go Public Companies In The Primary Consumer Goods Sector That Recorded In Idx Period 2017-2019 - Raja David Hamonangan Damanik, Yan; Toni, Nagian; Romi, Elly; Purba, Kuras (International Journal of Science, Technology & Management, 2022)
This study aims to analyze the effect of Debt to Total Assets, Return On Assets, Cash Ratio on Dividend Payout Ratio with Firm Size as an Intervening Variable in Go Public Companies in the Primary Consumer Goods sector recorded in IDX for the 2017-2019 period. The population in this study are consumption companies with food and beverage, cigarettes, pharmaceuticals, cosmetics and household goods and household appliances sub-sectors. The sampling technique used was purposive sampling, in order to obtain 22 companies with 3 years of observation to 66 observations. The data analysis tool uses SmartPLS 3.0. The results of the analysis show that DAR, ROA, and Cash Ratio have a positive but not significant effect on Dividend Policy, Firm Size has a positive and significant effect on DPR, Firm Size is not able to mediate the influence of DAR, ROA, and Cash Ratio on DPR policy. DAR, ROA, and Cash Ratio can explain the DPR by 16.5% while the remaining 83.5% is explained by other variables. Suggestions for investors to choose a company that has a high DAR, ROA, and Cash ratio and a large Firm Size.